2021
DOI: 10.2196/26872
|View full text |Cite
|
Sign up to set email alerts
|

Brain Exercising Games With Consumer-Grade Single-Channel Electroencephalogram Neurofeedback: Pre-Post Intervention Study

Abstract: Background The aging population is one of the major challenges affecting societies worldwide. As the proportion of older people grows dramatically, so does the number of age-related illnesses such as dementia-related illnesses. Preventive care should be emphasized as an effective tool to combat and manage this situation. Objective The aim of this pilot project was to study the benefits of using neurofeedback-based brain training games for enhancing cogn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Jirayucharoensak et al recruited 65 MCI and 54 healthy senior women as subjects and found that, after game-based neurofeedback training, rapid visual processing and spatial working memory (SWM) improved significantly [ 36 ]. Israsena et al conducted a study with 35 participants, whereby after long-term neuronal feedback, brain exercise games confirmed that games improve visual memory, attention, and spatial working memory [ 32 ]. Our study confirmed that GBIT can be one of the evaluation tools for the cognitive function of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Jirayucharoensak et al recruited 65 MCI and 54 healthy senior women as subjects and found that, after game-based neurofeedback training, rapid visual processing and spatial working memory (SWM) improved significantly [ 36 ]. Israsena et al conducted a study with 35 participants, whereby after long-term neuronal feedback, brain exercise games confirmed that games improve visual memory, attention, and spatial working memory [ 32 ]. Our study confirmed that GBIT can be one of the evaluation tools for the cognitive function of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, the user is required to handle a device and apply a physical pressure to a surface to trigger events. Whereas, in the second case, [2], [4], [5], [7], [10], [11], [18], [22], [24], [25], [28], [30], [34], [45], [51], [53], [60]- [121] 79 Mobile devices [13], [16], [19], [26], [31], [36], [37], [39], [41], [43], [44], [59],…”
Section: Interaction Technologiesmentioning
confidence: 99%
“…As participants could suffer from visual and hearing problems or have troubles with atten- tion, visual scenes have to be as simple as possible and search space should be reduced. During gameplay, simple and immediate data as a countdown timer, the number of remained chances to guess an answer, the current score or achieved goals are often shown to incentive the subject to answer as quickly and accurately as possible [3], [14], [17], [19], [20], [22], [24], [26], [28]- [31], [33], [38]- [41], [44], [49], [50], [52], [53], [71], [72], [79], [83], [96], [97], [99], [100], [106], [109], [115], [120], [124], [125], [130]- [132], [137], [138], [142], [150], [161], [164], [179], [191], [209], [211], [212], [231],…”
Section: Interaction Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They include imagery training, music regulation, breathing, meditation, amongst others [1][2][3][4][5][6]. Many therapeutic implementations of SR have been using serious games to increase user engagement and motivation for anxiety disorders [7], epilepsy [8], attention-deficit/hyperactivity disorder [9], and cognitive training in elders [10]. However, the combined use of SR and serious games is not a mature methodology.…”
Section: Introductionmentioning
confidence: 99%